PEMANFAATAN FUNGSI ANTI OKSIDAN GAMBIR (Uncaria gambir) SEBAGAI HEPATOPROTEKTOR - Edward, Zulkarnain (Jurnal Riset Kimia, 2009)
ABSTRACT The aim of the research is to find out the effect of the hepatoprotector from gambier to some rats animal contaminated by carbon tetrachloride (CCl4). The research was done in Biochemistry laboratory Medical Faculty Andalas University Padang applied to 12 galur wistar rats species in about ± 2 months ages with 170-200 g weight, which are separated into 3 groups (clusters). They are cluster in negative control, in positive control (CCl4 2 mg/kgBB inductions), and treated cluster (CCl4  inductions and 10 mg/kgBB gambier given). Statistically analyzed the data by one way Anova test with 95% confidence of degree, the result of the research are pointed to the rate of MDA serum level which is 1.08 ± 0.12 nmol/mL for the cluster in negative control, 4.07 ± 0.45 nmol/mL for positive control cluster, and 3.28 ± 0.46 nmol/mL for treated cluster showed the significant differences between the 3 clusters. The rates of MDA lever level to the cluster in negative control is about 1.80 ± 0.30 nmol/mL, in positive control is about 4.55 ± 0.56 nmol/mL, and the treated cluster is about 3.92 ± 0.22 nmol/mL, from the 3 clusters above shows that there is only the positive control and the treated control has no meaning of purpose. It concluded that the CCl4  has the hepatotoxite effect with gambier could be functionated as the hepatoprotector. Key words : gambier, CCl4, hepatoprotector, MDA